Assessment of Different Orthodontic Treatment Need Indices - Hameed, Muzna; Jan, Abdullah; Khurram, Khadija; Afgan, Numia; Alamzeb, Haseeb; Tariq, Anum (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the orthodontic treatment need indices in the adolescents.Study Design: Cross-sectional study.Place and Duration of Study: Orthodontics Department, Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from Dec 2019 to Feb 2020.Methodology: A total of 144 subjects were selected. The orthodontic treatment need was determined using the Index of Orthodontics Treatment Needs (IOTN) and Dental Aesthetic Index (DAI). Dental casts were made for each subject and rated against DAI. Measurements against all ten components of DAI were undertaken based on the patient's occlusal morphology.Intraoral photographs and casts were used to determine the aesthetic and dental health components of IOTN. Results: According to Index of Orthodontics Treatment Needs- Aesthetic Component, high severity and orthodontic treatment need were observed 18(12.5%). Index of Orthodontics Treatment Needs-Dental Health Component showed a high severity and treatment need 55(38.1%), while DAI revealed a high severity and treatment need 106(73.61%) subjects. Kappa analysis exhibited no significant association between IOTN-DHC Index and AC Index (κ=0.089, p=0.158) and only a slight agreement between IOTN-DHC and DAI (κ=0.18, p=0.005).Conclusion: While using DAI and IOTN, the perception of orthodontic treatment needs is assessed differently. Indices exhibited low agreement for high treatment need cases and high agreement for low treatment need cases.